Balochistan, Baloch and the China-Pakistan Economic Corridor - Maria Malik (Journal of Political Studies, 2019)
Over the years, Balochistan has swayed between obscurity and prominence but its geo-strategic significance has never slackened. Pakistan‟s largest province in terms of landmass it enjoys an important geostrategic position because of its proximity with the Middle East, Central Asia, South Asia and the Indian Ocean. With the recent developments ahead in sight of the CPEC the major world powers are shifting their focus to Gwadar, which is the central piece of the whole CPEC and is located close to the Strait of Hormuz through which 20% of total global oil production passes through. The likely CPEC network of roads and rails will provide China with an easy and much shorter trade route to the markets of Europe, Gulf and Africa. Given the significance of Gwadar and Balochistan province several analysts and researchers have questioned about the welfare of the locals residing in the region. The basic aim of this paper is to look at how the CPEC and its projects are going to impact the lives of the local population, particularly the Baloch. In order to lead CPEC projects to their successful completion, it is imperative to take in account the needs and grievances of the local people; who unless have their objections addressed can cause trouble. The basic thing is to adopt the policy of inclusivity by taking the local stakeholders (the politicians, the fishermen, the nationalists and the young unemployed youth) on board and by making the local people skillfully capable through vocational trainings thus opening the array of opportunities that CPEC shall bring to the region. The paper is qualitative in nature and has employed primary and secondary sources of data collection using literature review, semi-structured interviews and focus group discussions as tools for data analysis.